Ring opening polymerisation of ɛ-caprolactone using microwave electric and magnetic heating - Wang, Kaiyang (2018)
The work presented in this thesis aims to highlight the differences in heating methods, which are conventional, microwave electric, and microwave magnetic heating, for the ring opening polymerisation of ɛ-caprolactone, as well as the development of an alternative catalyst that is specifically used in microwave magnetic heating to replace the current benchmark catalyst. Chapter 1 introduces the background of this thesis. There is also an overview of various types of biodegradable polymers, polymerisation techniques, and catalysts used in the polymerisation. An introduction into the basics of microwave and microwave electric and magnetic heating is also provided in this chapter. Chapter 2 goes on to explain the analytical techniques that are used to characterise the polymer and the dielectric properties. Procedures in locating the reaction vessel at the microwave electric and magnetic dominant positions in the microwave reactor are described. Experimental procedures that are used throughout this thesis are also explained. Chapter 3 investigates the dielectric properties of various types of metal complexes in both solid powder form and when dissolved in a solvent, to study the factors that affect the interaction between these complexes and the microwave electromagnetic field. Then further investigation into a series of heating experiments of solutions containing these complexes is carried out, to see if the empirical observations follow the same trend as predicted from the dielectric property results. Chapter 4 explores the first application of microwave magnetic heating to the ring opening polymerisation of ɛ-caprolactone catalysed by metal halides, and compares this to the conventional and microwave electric heating, and investigates the effects of different heating methods have on the overall polymerisation. This chapter also investigates various metal halides that experienced different response to the microwave electric and magnetic heating to see how this affects the polymerisation process. Chapter 5 describes the development of novel organometllic catalysts that can be used in the ring opening polymerisation of ɛ-caprolactone with the application of microwave magnetic heating, and possibly replace the existing benchmark catalyst Sn(Oct)2. The use of various heating methods is also investigated to see what effects they have on the overall process.